Planning Research on Application of Nanomaterial Technology in Disaster Prevention and Reconstruction - Jun Shao; Huihui Yan; Haosheng Xu (Journal of Chemistry)
An earthquake causes a huge loss of life and property. After an earthquake, many buildings are seriously damaged or collapsed. On the one hand, it is necessary to make full use of nanomaterials technology to improve seismic strength during reconstruction; on the other hand, scientific planning is needed to reduce pollution, carbon emissions, and energy consumption. This paper mainly studies the application of nanomaterial technology in disaster prevention and reconstruction. Through a series of planning safeguard measures, the overall seismic performance of the city is improved in order to provide theoretical guidance and technical support for disaster prevention and reconstruction. This paper mainly introduces the stress analysis of frame joints after earthquake and the planning of urban disaster prevention and reconstruction. In addition to the different types of concrete materials (ordinary concrete, nano silica fiber concrete, PVA fiber concrete), the fixed amount of water, superplasticizer, reinforcement, sand, and gravel, the concrete strength grade is C30. Then, three kinds of concrete frame joints are tested under low cycle cyclic loading to compare the seismic performance of the three kinds of concrete. The experimental results show that the fuzzy evaluation of urban disaster prevention and reconstruction planning has been carried out for 6 communities in this city. Among them, 4 communities are qualified and 2 communities are unqualified. Therefore, it is necessary to focus on seismic reinforcement or carry out urban planning research again. Compared with ordinary concrete, the bearing capacity and ductility coefficient of nano silica fiber concrete and PVA fiber concrete are increased by 37.8% and 15.6%, respectively. It is proved that the seismic performance of nano silica fiber reinforced concrete is far better than that of ordinary concrete.